2020
DOI: 10.1002/anie.202005012
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Analogs of Three‐Dimensional Lead‐Halide Hybrid Perovskites

Abstract: Replacing the PbÀXo ctahedral building unit of A I PbX 3 perovskites (X = halide) with ap air of edge-sharing PbÀXo ctahedra affords the expanded perovskite analogs: A II Pb 2 X 6 .W er eport seven members of this new family of materials.I n3 Dh ybrid perovskites,o rbitals from the organic molecules do not participate in the band edges.Incontrast, the more spacious inorganic sublattice of the expanded analogs accommodates larger pyrazinium-based cations with low-lying p*o rbitals that form the conduction band,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 58 publications
2
49
0
Order By: Relevance
“…The recent work of H. Karunadasa et al also showed that partial insertion of reduced pyrazinium heterocycles in expanded 3D perovskite analogues offers a new route for chemical doping of the semiconductor. 68 Building a 2D perovskite with a full load of active organic moieties, tuned with the perovskite emission, is therefore an emerging field allowing hopes in the building of new and more performing materials in this family.…”
Section: Discussionmentioning
confidence: 99%
“…The recent work of H. Karunadasa et al also showed that partial insertion of reduced pyrazinium heterocycles in expanded 3D perovskite analogues offers a new route for chemical doping of the semiconductor. 68 Building a 2D perovskite with a full load of active organic moieties, tuned with the perovskite emission, is therefore an emerging field allowing hopes in the building of new and more performing materials in this family.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of ion migration may be related to local distortion leading to a lattice compression, which has recently shown to increase the activation energy for ion migration, enabling strain engineering (Hutter et al, 2020). Moreover, low-dimensional perovskites and their analogs (Connor et al, 2018;Milić et al, 2019a;Umeyama et al, 2020) were also found to be effective in suppressing ion migration due to the ion-impermeable organic spacer layers (Lin et al, 2017;Rudd and Huang, 2019). In this regard, in-depth analysis is required to elucidate the mechanisms and establish structureproperty relationships that define guidelines for suitable molecular design toward addressing the challenges of controlling ion migration in various hybrid perovskite compositions.…”
Section: Mitigationmentioning
confidence: 99%
“…O) = 2 Å). The peculiar curled conformation of HPA + , related to the hydrogen bond ability of both the NH 3 + and the OH ends, certainly hinders formation of 2D perovskites, while favoring here a structure having a 3D metal halide network, as already observed for other intermediate size cations [23]. While MA + cations are located near the shared iodides connecting adjacent 2 × 2 oc tahedra units within the 2D perovskite subnetwork, the HPA + are clearly located in chan nels defined by this open framework.…”
Section: Crystal Structure Thermal Stability and Optical Propertiesmentioning
confidence: 53%
“…In the tin iodide system, a series of ASnI 3 (A + = guanidinium, ethylammonium) compounds has been found, the 3D iodostannate network being based on corner-and face-sharing octahedra [22]. More recently, a series of pyrazinium-based dications (A' 2+ ) has afforded the (A")Pb 2 X 6 compounds whose structures are based on 3D networks of corner-and edge-sharing lead halide octahedra [23].…”
Section: Introductionmentioning
confidence: 99%